When a corporation rapes: perceptions of rape in civil court for corporate defendants. Issue 7 (9th August 2018) - Lippert, Anne; Golding, Jonathan; Lynch, Kellie; Haak, Eric
ABSTRACT: In recent years, the coupling of poor outcomes for rape victims in criminal court and the widening scope of legal responsibility for sexual assault has prompted plaintiffs to file civil suits for rape against corporations. Unfortunately, we know little about juror perception of civilly litigated rape against corporate defendants and most jury research involving corporate defendants concerns non-sexual injury cases (e.g. premises liability, automobile accidents). With the increasing number of corporations being sued civilly for rape, we need to understand how civil juries perceive these cases. The present study investigated mock jurors' perceptions of a fictional civil rape trial against a hotel. Community members ( N = 155) read one of three trial summaries: Civil rape trial against the alleged perpetrator, civil rape trial against a hotel, or criminal rape trial. Results indicate females have higher pro-plaintiff judgments than males in civil court, perceptions of greed typically associated with civil litigation apply to rape, and favorable plaintiff decisions are most likely against a corporate defendant. Also, mental models suggest mock jurors conceptualize criminal and civil rape cases against an individual similarly. We discuss our results in terms of psychological, legal and practical expectations when suing for rape.